Validasi Kuesioner Accountant Career Adaptability Skills Pada Mahasiswa Politeknik - Hendra Sanjaya Kusno; Wijayani, Dahyang Ika Leni; Nur Vita Opu (Politeknik Ganesha Medan, 2024)
According to students enrolled in accounting study programs, the purpose of this study is to map the skills of an accounting graduate, particularly from vocational school. The purpose of this competence mapping is to help vocational education institutions (PTPV) determine which key competencies students need to possess to be prepared for a career in the workforce. Students in vocational colleges in East Kalimantan are the subjects of this study to gather their opinions on the essential skills of accountants. The core competencies are derived from the International Federation of Accountants (IFAC) lists five professional skills: intellectual, technical & functional, organizational & management, interpersonal & communication. Confirmatory Factor Analysis (CFA) is used in data analysis using SPSS AMOS 26 software. The five dimensions- that comprise 31 question items can be used to career adaptability skills for accountants. The findings of this study can be utilized to develop a career adaptability skills questionnaire for accountants that can be used by both the workplace and vocational education.